2021
DOI: 10.3390/ijms222011172
|View full text |Cite
|
Sign up to set email alerts
|

Host Defense Peptides: Dual Antimicrobial and Immunomodulatory Action

Abstract: The rapid rise of multidrug-resistant (MDR) bacteria has once again caused bacterial infections to become a global health concern. Antimicrobial peptides (AMPs), also known as host defense peptides (HDPs), offer a viable solution to these pathogens due to their diverse mechanisms of actions, which include direct killing as well as immunomodulatory properties (e.g., anti-inflammatory activity). HDPs may hence provide a more robust treatment of bacterial infections. In this review, the advent of and the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 142 publications
(198 reference statements)
0
45
0
Order By: Relevance
“…In this study, we found that CATH-1, CATH-3, and PMAP-36 had a synergistic effect with erythromycin on bacterial killing and significantly reduced resistance to antibiotics. It has been reported that the bactericidal mechanism of AMPs acts through the cell membrane not involved in a specific target, so it is unlikely to develop microbial resistance (Drayton et al, 2021). Our study showed that AMPs (CATH-1,−3 and PMAP-36) have good bactericidal activities against S. aureus, S. enteritidis, and E. coli, which is consistent with other findings that CATH-1,−3 and PMAP-36 showed a broad spectrum of bactericidal activities against S. aureus, S. enteritidis, E. coli, Campylobacter jejuni, and Clostridium perfringens (Lv et al, 2014;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that CATH-1, CATH-3, and PMAP-36 had a synergistic effect with erythromycin on bacterial killing and significantly reduced resistance to antibiotics. It has been reported that the bactericidal mechanism of AMPs acts through the cell membrane not involved in a specific target, so it is unlikely to develop microbial resistance (Drayton et al, 2021). Our study showed that AMPs (CATH-1,−3 and PMAP-36) have good bactericidal activities against S. aureus, S. enteritidis, and E. coli, which is consistent with other findings that CATH-1,−3 and PMAP-36 showed a broad spectrum of bactericidal activities against S. aureus, S. enteritidis, E. coli, Campylobacter jejuni, and Clostridium perfringens (Lv et al, 2014;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The promising future development path of AMPs as new therapeutics is to create multifunctional AMPs by combining their direct antimicrobial activity with indirect activity, e.g., modulation of the immune system response. Immunomodulation can enhance the antimicrobial effects of AMPs by inducing the recruitment of antigen-presenting cells to the site of infection, activating neutrophils or macrophages, influencing the differentiation of dendritic cells, and suppressing pro-inflammatory cytokines [ 16 , 28 , 29 , 30 ]. Anti-infective therapeutic peptides with combined antimicrobial and immunomodulatory properties represent a new approach to treat antibiotic-resistant infections.…”
Section: De Novo Designed Antimicrobial Immunomodulatory Peptidesmentioning
confidence: 99%
“…In the era of bacterial AMR and the drying pipelines of new small molecule antibiotics, antimicrobial peptides (AMPs) provide certain hopes to fight against MDR pathogens [14][15][16]. AMPs, also termed as host defense peptides (HDPs), are evolutionarily conserved arsenals of all organisms to fend microbial invasion [17][18][19].…”
Section: Introductionmentioning
confidence: 99%